Xylem Embolism Resistance Determines Leaf Mortality during Drought in Persea americana - Cardoso, Amanda A. (Plant Physiol, 2020)
The driver of leaf mortality during drought stress is a critical unknown. We used the commercially important tree Persea americana, in which there is a large variation in the degree of drought-induced leaf death across the canopy, to test whether embolism formation in the xylem during drought drives this leaf mortality. A large range in the number of embolized vessels in the petioles of leaves was observed across the canopy of plants that had experienced drought. Despite considerable variation between leaves, the amount of embolized vessels in the xylem of the petiole strongly correlated with area of drought-induced tissue death in individual leaves. Consistent with this finding was a large interleaf variability in xylem resistance to embolism, with a 1.45 MPa variation in the water potential at which 50% of the xylem in the leaf midrib embolized across leaves. Our results implicate xylem embolism as a driver of leaf mortality during drought. Moreover, we propose that heterogeneity in drought-induced leaf mortality across a canopy is caused by high interleaf variability in xylem resistance to embolism, which may act as a buffer against complete canopy death during prolonged drought in P. americana.